Beyond the taboo: a thanatosociological investigation of companion animal loss based on an interview study with small animal veterinarians - Springer, Svenja; Dürnberger, Christian (Frontiers in Veterinary Science, 2026)
Thanatosociology examines the social dimensions of death, focusing on how societies perceive and navigate the realities of mortality. A key argument in this field posits that, in certain contemporary Western societies, direct experiences with dying and death are increasingly rare, leading to the emergence of death as a taboo topic. Given the emotional bond between pet owners and their pets, it becomes essential to examine the implications of companion animal loss within this framework. As pets often die at home, this topic warrants investigation to better understand how these experiences can influence societal perceptions of mortality. This study aims to highlight this often-overlooked perspective, emphasizing the significance of companion animal loss in shaping collective attitudes toward death and dying. To investigate this phenomenon, qualitative interviews were conducted with 20 small animal veterinarians specializing in hospice and palliative care. The findings corroborate the notion of a taboo surrounding death, as veterinarians highlighted the physical and emotional distancing from dying individuals and the pervasive fear and uncertainty when confronting mortality. Further, respondents argued that other cultures engage with death more openly and suggest that the experience of accompanying a dying pet can challenge societal repression, thereby fostering a more reflective approach to death for both adults and children. Relatedly, veterinarians stated that this experience provides a unique opportunity to bring death into the public consciousness, transforming it from a taboo into a more visible aspect of life. Further, respondents described the loss of a companion animal as a “training ground” for confronting death, noting that past negative experiences can complicate decision-making regarding animal care. This research suggests that veterinarians are not only perceived as medical professionals but also as “experts on death,” providing critical emotional support during end-of-life care. The findings highlight the need to integrate discussions about death into veterinary education, emphasizing the critical role veterinarians play in facilitating conversations about mortality and supporting bereaved companion animal owners. By recognizing this dual role, we can enhance the capacity of the veterinary profession to address the complexities of grief and mortality, ultimately fostering a more open dialogue about these important issues.